Multi-drive composite double-response gel system and preparation method thereof
By adopting a multi-drive composite dual-response gel system, combining polyN-isopropyl acrylamide-acrylamide gel with polyvinyl alcohol-cyclodextrin gel and polyvinyl alcohol-bile acid gel, the shortcomings in mechanical properties, service life and complex environment adaptability of existing hydrogels are solved, and a high-performance dual-response gel is achieved.
Patent Information
- Application Number
- CN202411940049.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
Existing hydrogels have problems such as poor mechanical properties, poor contact with the sensing interface, and short service life. The single-condition phase change response gel is affected by a single factor and is limited in practical application scenarios.
A multi-drive composite dual-response gel system is adopted to form a double-response gel with temperature sensitivity and self-healing by combining polyN-isopropyl acrylamide-acrylamide gel with polyvinyl alcohol-cyclodextrin gel and polyvinyl alcohol-bile acid gel.
The gel is optimized with good adhesion, temperature sensitivity and comprehensive performance, improves the mechanical properties and service life of the gel, and has the ability to heal in complex environments.
Smart Images

Figure CN119684640A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer biomaterials, and in particular relates to a multi-drive composite dual-response gel system and a preparation method thereof. Background Art
[0002] Hydrogel is a type of functional polymer material with a hydrophilic and three-dimensional network structure formed by physical or chemical cross-linking. It has broad application prospects in soft robotics, wound dressings, and health monitoring. Traditional hydrogels have problems such as poor mechanical properties, poor contact with the sensor interface, and short service life. When used, hydrogels will fall off or be damaged by external environmental factors, resulting in poor durability and short service life.
[0003] The existing thermosensitive gel has a general gelation speed and is easily affected by environmental factors in the early stage of gelation, which greatly reduces the effect of the final gel. Moreover, the single-condition phase change response gel is affected by a single factor and is limited in practical application scenarios. For example, Chinese patent application CN2017109905915, a low molecular weight polyvinyl alcohol self-healing hydrogel and its preparation method, discloses a method of reacting low molecular weight polyvinyl alcohol under succinic anhydride and p-toluenesulfonic acid to obtain carboxylic acid-modified PVA; then the carboxylic acid-modified PVA is reacted with amino-modified bile acid and mono-(6-ethylenediamine-6-deoxy)-β-cyclodextrin to obtain PVA-CA and PVA-CD; finally, PVA-CA and PVA-CD are dissolved in hot water respectively, and the two solutions are mixed and self-assembled to obtain the low molecular weight polyvinyl alcohol self-healing hydrogel. The gel obtained by the present invention has excellent biocompatibility, good mechanical properties and self-repairing properties, and can adjust the mechanical properties of the self-repairing hydrogel by adjusting the bile acid grafting ratio, but the system has only a single response characteristic and no temperature-sensitive property. The single response characteristic alone will slow down the initial gelation rate of the gel, and the system has no polyphenol groups and poor adhesion. For example, Chinese patent application CN2024110573910, a method for in vivo cultivation of bezoar based on thermosensitive gel, and Chinese patent application CN2024110574519, a thermosensitive gel for bezoar cultivation and its preparation method and application, are all preliminary studies by the inventor, but the gel has poor viscosity, the single response gel transition speed is slow, and there is no self-healing property, and it cannot collect substances in a complex environment.
[0004] In order to solve the above technical problems, the inventors of the present invention are committed to seeking to prepare a multifunctional, adherent, multi-actuated, composite, dual-response gel system with good comprehensive performance. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a dual-response gel system with multi-drive composite, which has good adhesion, temperature sensitivity and excellent comprehensive performance.
[0006] The gel system of the present invention is divided into a first layer of gel and a second layer of gel, wherein:
[0007] The first layer of gel is composed of poly (N-isopropylacrylamide)-acrylamide gel solution and guest coordination gel solution;
[0008] The second layer of gel is a main coordination gel solution;
[0009] wherein the guest coordination gel solution is a polyvinyl alcohol-cyclodextrin gel solution;
[0010] The main coordination gel solution is one or more of polyvinyl alcohol-bile acid gel solution, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution, and polyvinyl alcohol-glycine gel solution.
[0011] In the above gel system: the weight ratio of each gel solution is calculated based on the solid content:
[0012] For every 150 g of poly (N-isopropylacrylamide)-acrylamide gel, add 10-25 g of poly (vinyl alcohol)-cyclodextrin gel and 15-30 g of the main coordination gel.
[0013] Preferably, for every 150 g of poly (N-isopropylacrylamide)-acrylamide gel, 10-25 g of poly (vinyl alcohol)-cyclodextrin gel and 20-30 g of the main coordination gel are added.
[0014] For every 150 g of poly (N-isopropylacrylamide)-acrylamide gel, add 10-25 g of poly (vinyl alcohol)-cyclodextrin gel and 15-30 g of poly (vinyl alcohol)-bile acid gel (replaced with one or more of polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel).
[0015] Preferably, for every 150 g of poly (N-isopropylacrylamide)-acrylamide gel, 15-25 g of poly (vinyl alcohol)-cyclodextrin gel and 20-30 g of poly (vinyl alcohol)-bile acid gel (replaced with one or more of polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel are added.
[0016] Most preferably, 20 g of polyvinyl alcohol-cyclodextrin gel and 30 g of polyvinyl alcohol-bile acid gel (replaced with one or more of polyethylene glycol-bile acid gel, polyvinyl alcohol-deoxycholic acid gel, polyvinyl alcohol-taurocholic acid gel or polyvinyl alcohol-glycine gel) are added to every 150 g of poly (N-isopropylacrylamide)-acrylamide gel.
[0017] When the gel system is used, the gel is first prepared into a gel solution and then used.
[0018] The concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.1-0.5 g / g; or preferably, the concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.1-0.3 g / g; or most preferably, the concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.3 g / g.
[0019] Or, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.05-0.15 g / g; or preferably, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.05-0.1 g / g; or most preferably, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.1 g / g.
[0020] Or, the main coordination gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.05-0.15g / g; or preferably, the main coordination gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.05-0.1g / g; or most preferably, the main gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.1g / g.
[0021] Or preferably, the main coordination gel solution adopts polyethylene glycol-bile acid gel solution, and its concentration is 0.05-0.15g / g; or further preferably, the main coordination gel solution adopts polyethylene glycol-bile acid gel solution, and its concentration is 0.05-0.1g / g; or most preferably, the main gel solution adopts polyethylene glycol-bile acid gel solution, and its concentration is 0.1g / g.
[0022] The above-mentioned gel system is calculated based on the gel solution, and the ratio of each gel solution is as follows: for every 500g of poly (N-isopropylacrylamide)-acrylamide gel solution with a concentration of 0.1-0.5g / g, 100-250g of poly (vinyl alcohol)-cyclodextrin gel solution with a concentration of 0.05-0.15g / g and 150-300g of main coordination gel solution with a concentration of 0.05-0.15g / g are added; the main coordination gel can be one or more of poly (vinyl alcohol)-cyclodextrin gel, polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel; the main coordination gel preferably uses poly (vinyl alcohol)-cyclodextrin gel.
[0023] Preferably, the ratio of each gel solution is as follows: for every 500g of poly (N-isopropylacrylamide)-acrylamide gel solution with a concentration of 0.3g / g, 100-250g of poly (vinyl alcohol)-cyclodextrin gel solution with a concentration of 0.1g / g and 150-300g of main coordination gel solution with a concentration of 0.1g / g are added; the main coordination gel can be one or more of poly (vinyl alcohol)-cyclodextrin gel, polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel; the main coordination gel preferably uses poly (vinyl alcohol)-cyclodextrin gel.
[0024] Further preferably, the ratio of each gel solution is as follows: for every 500g of poly (N-isopropylacrylamide)-acrylamide gel solution with a concentration of 0.3g / g, 150-250g of poly (Viavinyl alcohol)-cyclodextrin gel solution with a concentration of 0.1g / g and 200-300g of main coordination gel solution with a concentration of 0.1g / g are added; the main coordination gel can be one or more of poly (Viavinyl alcohol)-cyclodextrin gel, polyethylene glycol-bile acid gel, poly (Viavinyl alcohol)-deoxycholic acid gel, poly (Viavinyl alcohol)-taurocholic acid gel or poly (Viavinyl alcohol)-glycine gel; the main coordination gel preferably uses poly (Viavinyl alcohol)-cyclodextrin gel.
[0025] Most preferably, the ratio of each gel solution is as follows: for every 500g of poly (N-isopropylacrylamide)-acrylamide gel solution with a concentration of 0.3g / g, 200g of PVA-CA polyvinyl alcohol-cyclodextrin gel solution with a concentration of 0.1g / g and 300g of main coordination gel solution with a concentration of 0.1g / g are added; the main coordination gel can be one or more of polyvinyl alcohol-cyclodextrin gel, polyethylene glycol-bile acid gel, polyvinyl alcohol-deoxycholic acid gel, polyvinyl alcohol-taurocholic acid gel or polyvinyl alcohol-glycine gel; the main coordination gel preferably uses polyvinyl alcohol-cyclodextrin gel.
[0026] The working principle of the gel system of the present invention is a double gel formation and double response mechanism, specifically, the poly N-isopropylacrylamide-acrylamide gel solution in the first layer of gel is used as the first response gel solution, and the temperature-sensitive characteristics of the gel solution are used to perform phase transition response, so as to achieve the phase transition of the gel solution to the gel within a specific temperature range. The polyvinyl alcohol-cyclodextrin gel solution in the first layer of gel and the polyvinyl alcohol-bile acid gel solution in the second gel are used as the second response gel solution, and the two are host-guest coordination gels, the host coordination gel is the polyvinyl alcohol-bile acid gel solution, and the guest coordination gel is the polyvinyl alcohol-cyclodextrin gel solution. The two are in the state of gel solution at the beginning, and are in the state of gel when mixed together and have self-healing properties. The two gel solutions are mixed together, and the entanglement and cross-linking in the physical space can make the gel have a large pore structure; and the two gel solutions can make the mixed gel have two response characteristics, which can be applied in a wider range of fields.
[0027] In the above gel system:
[0028] The poly (N-isopropylacrylamide)-acrylamide gel solution is prepared by a one-pot method:
[0029] A. Weigh the reaction raw materials N-isopropylacrylamide, acrylamide, carboxyl donor, chloride salt, and polyphenol group donor according to proportion and place them in a reaction device;
[0030] B. After passing inert gas into the reaction device and stirring for a certain period of time, add initiator ammonium persulfate and accelerator tetramethylethylenediamine to obtain gel solution B;
[0031] C. The gel solution obtained in step B is dialyzed to remove impurities, thereby obtaining a poly (N-isopropylacrylamide)-acrylamide gel solution.
[0032] The acrylamide in the reaction raw material of step A can be replaced by one or more of poloxamer and polylactic acid-glycolic acid-ethylene glycol. The LCST value can also be regulated by adjusting the proportion to achieve a temperature sensitive range of 32-45°C.
[0033] The carboxyl donor in the reaction raw material of step A is one or more of acrylic acid, propylene sulfonic acid and itaconic acid.
[0034] In step A, the chloride salt in the reaction raw material is used as a metal ion donor, and the chloride salt that can be used is one or more of aluminum chloride, ferric chloride, and calcium chloride; the above chloride salts are used to provide dynamic metal ions, so that the poly (N-isopropylacrylamide)-acrylamide gel has self-healing properties.
[0035] The polyphenol group donor in the reaction raw materials of step A is one or more of polydopamine, tannic acid and anthocyanin.
[0036] The polydopamine is prepared by the following method: dopamine hydrochloride is used to carry out a self-polymerization reaction under the condition of a pH value of 10-12, and the reaction is considered to be completed when the solution changes from transparent to black, thereby obtaining polydopamine.
[0037] Preferably, in the polydopamine preparation method, the pH value is 11-12.
[0038] Most preferably, in the polydopamine preparation method, the pH value is 11.
[0039] Preferably, in the polydopamine preparation method, the self-polymerization reaction time is 20-60 min. Preferably, the self-polymerization reaction time is 30-60 min; most preferably, the self-polymerization reaction time is 30 min.
[0040] The ratio of the reaction materials in step A is:
[0041] In step A, the reaction raw materials are added with 10-80 g of acrylamide or one or more of poloxamer, polylactic acid-glycolic acid-ethylene glycol, 1-50 g of carboxyl donor, 90-450 mg of chloride salt, and 1-120 g of polyphenol group per 500 g of N-isopropylacrylamide.
[0042] Preferably, the reaction raw materials in step A are added with 20-60g acrylamide, 10-30g poloxamer or 20-40g polylactic acid-glycolic acid-ethylene glycol per 500g N-isopropylacrylamide; the carboxyl donor is 1-30g acrylic acid, 1-20g propylene sulfonic acid or 1-20g itaconic acid; the chloride salt is 90-270mg aluminum chloride, 90-270mg ferric chloride or 90-270mg calcium chloride; the polyphenol group is 1-50g polydopamine, 5-30g tannic acid or 1-30g anthocyanin.
[0043] Most preferably, in step A, 30 g of acrylamide is added to the reaction raw materials per 500 g of N-isopropylacrylamide; 20 g of acrylic acid is used as the carboxyl donor; 180 mg of aluminum chloride is used as the chloride salt; and 50 g of polydopamine, 5-30 g of tannic acid, or 1-30 g of anthocyanin is used as the polyphenol group.
[0044] In step B, the amount of the initiator ammonium persulfate and the accelerator tetramethylethylenediamine is calculated based on 1-20 g of initiator ammonium persulfate and 1-20 g of accelerator tetramethylethylenediamine per 500 g of N-isopropylacrylamide.
[0045] Preferably, the amount of the initiator ammonium persulfate and the promoter tetramethylethylenediamine used in step B is based on 15g of initiator ammonium persulfate and 10g of promoter tetramethylethylenediamine per 500g of N-isopropylacrylamide.
[0046] The aeration and stirring for a certain period of time in step B refers to stirring for 0.5-2 hours; preferably, the stirring time in step B is 1 hour.
[0047] The reaction conditions of the reaction in step B are: reaction temperature 40-80°C, reaction time 4-12h. Preferably, the reaction conditions of step B are: reaction temperature 60°C, reaction time 6h.
[0048] The dialysis in step C is water dialysis, and the dialysis time is 5-7 days. Preferably, the dialysis time in step C is 7 days.
[0049] The solution obtained in step C is dried to obtain poly (N-isopropylacrylamide)-acrylamide gel; the drying is carried out by low-temperature oven drying or freeze drying.
[0050] The preparation method of the polyvinyl alcohol-cyclodextrin gel solution comprises the following steps:
[0051] A. Acidification modification of polyvinyl alcohol:
[0052] (1) Polyvinyl alcohol is dissolved in dimethyl sulfoxide;
[0053] (2) adding succinic anhydride and p-toluenesulfonic acid to the solution obtained in step (1) to react;
[0054] (3) adding ether to the reaction solution obtained in step (2), filtering and washing to obtain a precipitate, dialyzing the obtained precipitate with water to remove impurities, and drying to obtain acid-modified polyvinyl alcohol (PVA-Acid).
[0055] B. Cyclodextrin grafting of polyvinyl alcohol
[0056] (1) Acid-modified polyvinyl alcohol is dissolved in water;
[0057] (2) adding aminocyclodextrin (Amino-CD), N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), and 1-hydroxybenzotriazole hydrate (HOBt) to the solution obtained in step (1), stirring for a certain period of time, reacting, and cooling to terminate the reaction;
[0058] (3) Ether is added to the solution obtained in step (2) to wash out the precipitate, and the precipitate is dialyzed to remove impurities to obtain polyvinyl alcohol grafted cyclodextrin (PVA-CD).
[0059] In the acidification modification of polyvinyl alcohol in step A:
[0060] The polyvinyl alcohol and dimethyl sulfoxide in step (1) are mixed according to the following ratio: 20-50 ml of dimethyl sulfoxide is added for every 2-6 g of polyvinyl alcohol.
[0061] Preferably, the polyvinyl alcohol and dimethyl sulfoxide in step (1) are mixed according to the following ratio: 50 ml of dimethyl sulfoxide is added for every 4 g of polyvinyl alcohol.
[0062] In step (2), the amount of succinic anhydride and p-toluenesulfonic acid added is 200-1000 mg succinic anhydride and 1-50 mg p-toluenesulfonic acid per 2-6 g polyvinyl alcohol.
[0063] Preferably, the amount of succinic anhydride and p-toluenesulfonic acid added in step (2) is 400-500 mg succinic anhydride and 5-25 mg p-toluenesulfonic acid per 4 g polyvinyl alcohol.
[0064] The temperature of the dimethyl sulfoxide (DMSO) in step (1) is 60-90°C, that is, polyvinyl alcohol is dissolved in dimethyl sulfoxide at 60-90°C; preferably, the temperature of the dimethyl sulfoxide (DMSO) in step (1) is 80°C.
[0065] The reaction conditions of step (2) are: reaction temperature 40-80°C, reaction time 36-72h; preferably, the reaction conditions of step (2) are reaction temperature 50°C, reaction time 48h.
[0066] The dialysis conditions in step (3) are: dialysis with water for 5-7 days. Preferably, the dialysis time is 5 days.
[0067] The drying in step (3) is carried out by low-temperature oven drying or freeze drying.
[0068] In the step B of cyclodextrin grafting of polyvinyl alcohol:
[0069] The water in step (1) is ultrapure water.
[0070] The temperature of the water in step (1) is 70-90°C, that is, the acidified modified polyvinyl alcohol is dissolved in water at 70-90°C; preferably, the temperature of the water in step (1) is 80°C.
[0071] The stirring for a certain time in step (2) refers to stirring for 0.5-2 hours. Preferably, the stirring for a certain time in step (2) refers to stirring for 1 hour.
[0072] The reaction conditions of the reaction in step (2) are: reaction temperature 40-80°C, reaction time 8-36h. Preferably, the reaction conditions of the reaction in step (2) are: reaction temperature 70°C, reaction time 24h.
[0073] The step (2) of cooling the reaction to terminate the reaction is to move the reaction solution into an ice water bath to terminate the reaction.
[0074] The dialysis in step (3) is water dialysis, and the dialysis time is 5-7 days. Preferably, the dialysis time in step (3) is 7 days.
[0075] The preparation method of the polyvinyl alcohol-bile acid gel solution comprises the following steps:
[0076] A. Acidification modification of polyvinyl alcohol
[0077] B. Bile acid grafting of polyvinyl alcohol
[0078] (1) Acid-modified polyvinyl alcohol is dissolved in dimethylformamide (DMF);
[0079] (2) adding aminocholic acid (Amino-CA), N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), and 1-hydroxybenzotriazole hydrate (HOBt) to the solution obtained in step (1), stirring for a certain period of time, reacting, and cooling to terminate the reaction;
[0080] (3) Ether is added to the solution obtained in step (2) to wash out the precipitate, and the precipitate is dialyzed to remove impurities to obtain polyvinyl alcohol grafted bile acid (PVA-CA).
[0081] In the bile acid grafting of polyvinyl alcohol in step B:
[0082] The temperature of the dimethylformamide in step (1) is 70-90°C, that is, the acid-modified polyvinyl alcohol is dissolved in dimethylformamide at 70-90°C; preferably, the temperature of the dimethylformamide in step (1) is 80°C.
[0083] The stirring time in step (2) refers to stirring for 0.5-2 hours. Preferably, the stirring time in step (2) is 1 hour.
[0084] The reaction conditions of the reaction in step (2) are: reaction temperature 40-80°C, reaction time 8-36h. Preferably, the reaction conditions of the reaction in step (2) are: reaction temperature 70°C, reaction time 24h.
[0085] The step (2) of cooling the reaction to terminate the reaction is to move the reaction solution into an ice water bath to terminate the reaction.
[0086] The dialysis in step (3) is water dialysis, and the dialysis time is 5-7 days. Preferably, the dialysis time in step (3) is 7 days.
[0087] The method for using the gel system of the present invention comprises the following steps:
[0088] A. Weigh each gel solution according to the solid content of the gel system or the ratio of the gel solution:
[0089] The first layer of gel is composed of poly (N-isopropylacrylamide)-acrylamide gel solution and guest coordination gel solution;
[0090] The second layer of gel is a main coordination gel solution;
[0091] wherein the guest coordination gel solution is a polyvinyl alcohol-cyclodextrin gel solution;
[0092] The main coordination gel solution is one or more of polyvinyl alcohol-bile acid gel solution, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution, and polyvinyl alcohol-glycine gel solution.
[0093] B. Inject the second layer of gel into the enrichment solution;
[0094] C. The first layer of gel poly (N-isopropylacrylamide)-acrylamide gel solution and polyvinyl alcohol-cyclodextrin gel solution are mixed and injected into the enrichment solution to obtain a gel.
[0095] The enrichment solution in step B and step C is water.
[0096] The dosage ratio of the enrichment solution and the poly (N-isopropylacrylamide)-acrylamide gel solution in step B and step C is as follows: 400-600 ml of the enrichment solution is added to every 500 g of the poly (N-isopropylacrylamide)-acrylamide gel solution with a concentration of 0.1-0.5 g / g.
[0097] Preferably, the ratio of the enrichment solution to the poly (N-isopropylacrylamide-acrylamide gel) solution in step B and step C is as follows: 500 ml of the enrichment solution is added to every 500 g of poly (N-isopropylacrylamide-acrylamide gel) solution having a concentration of 0.1-0.5 g / g.
[0098] The gel system of the present invention introduces temperature-sensitive N-isopropylacrylamide (NIPAM), and the LCST value is regulated by introducing the proportion of acrylamide (AM), so that the temperature-sensitive range is controlled at 32-45°C, covering the human body temperature of 37°C. The dynamic metal ions in chloride salt are introduced to make the poly N-isopropylacrylamide-acrylamide gel self-healing. The introduced polydopamine (DPOA), tannic acid, and anthocyanidin contain a large number of polyphenol groups, which can provide viscosity for the gel as a whole; and polydopamine, tannic acid, and anthocyanidin also have amino groups, which can form dynamic reversible ionic bonds with the carboxyl groups of acrylic acid; the amino groups can also form dynamic reversible hydrogen bonds with the amide groups of N-isopropylacrylamide and acrylamide, further improving its self-healing property.
[0099] The polyvinyl alcohol (PVA) in the gel system of the present invention has a large number of hydroxyl groups, which can form a large number of hydrogen bonds with the amide groups of the poly (N-isopropylacrylamide)-acrylamide gel, increase the physical cross-linking points of the gel, and thus improve the overall mechanical strength of the gel. The polyvinyl alcohol is modified, and bile acid is grafted on PVA to form a host (PVA-CA); cyclodextrin is grafted on PVA to form a guest (PVA-CD). The two substances can form a host-ligand gel (i.e., they are separated into a gel solution state, and mixed together to present a gel state with self-healing properties), further enhancing its gel formation speed and self-healing properties.
[0100] The gel system of the present invention mixes two layers of gel solution together, so that the mixed gel has two response characteristics of temperature sensitivity and host-guest coordination. It is an aqueous solution at room temperature and becomes a hydrogel at a predetermined temperature. It can be maintained for a certain period of time before being degraded, and can be applied in a wider range of fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0101] Figure 1 Schematic diagram of the double-layer response of the gel system of the present invention.
[0102] Figure 2 This is a scanning electron microscope image of the gel in Example 1 (1000 times).
[0103] in, Figure 2 a, Figure 2 b, Figure 2 c are the pore structure diagrams of different parts of the gel formation in Example 1.
[0104] Figure 3 This is a graph showing the adhesion performance of the gel of the present invention.
[0105] in, Figure 3 aThe gel adheres to the gloves and does not fall off; Figure 3 b. The gel adheres to the centrifuge tube cap and does not fall off.
[0106] Figure 4 It is the degradation curve diagram of embodiment and comparative example.
[0107] in, Figure 4 A- Figure 4 L are the gel degradation curves of Examples 1-12, Figure 4 M- Figure 4 Q is the gel degradation curve diagram of Comparative Examples 1, 3, 4, 5 and 6 respectively.
[0108] Figure 5 This is a diagram showing the self-healing properties of the gel of the present invention.
[0109] Figure 6 It is a comparison chart of the temperature-sensitive properties of the gel of the present invention and the comparative example. DETAILED DESCRIPTION
[0110] Below in conjunction with embodiment, the scheme of the present invention will be explained and described.It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.In the embodiment, if no specific technology or condition is indicated, it is carried out according to the technology or condition described in the document in this area or according to the product specification.The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained by commercial purchase.
[0111] The following are the definitions of the English abbreviations and main terms used in this invention:
[0112] N-isopropylacrylamide (NIPAM), acrylamide (AM), acrylic acid (AA), polydopamine (DPOA), polyvinyl alcohol (PVA), acidified polyvinyl alcohol (PVA-Acid), polyvinyl alcohol grafted cyclodextrin (PVA-CD), polyvinyl alcohol grafted bile acid (PVA-CA), aminocyclodextrin (Amino-CD), N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), 1-hydroxybenzotriazole hydrate (HOBt), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), aminocholic acid (Amino-CA).
[0113] The gel system of the present invention is divided into a first layer of gel and a second layer of gel, wherein:
[0114] The first layer of gel is composed of poly (N-isopropylacrylamide)-acrylamide gel solution and guest coordination gel solution;
[0115] The second layer of gel is a main coordination gel solution;
[0116] The guest coordination gel solution is a polyvinyl alcohol-cyclodextrin gel solution; the host coordination gel solution is one or more of a polyvinyl alcohol-bile acid gel solution, a polyethylene glycol-bile acid gel solution, a polyvinyl alcohol-deoxycholic acid gel solution, a polyvinyl alcohol-taurocholic acid gel solution, and a polyvinyl alcohol-glycine gel solution.
[0117] The poly (N-isopropylacrylamide)-acrylamide gel solution and poly (vinyl alcohol)-cyclodextrin gel solution are used as the first layer of gel, and the poly (vinyl alcohol)-bile acid gel solution is used as the second layer of gel. The dual response mechanism of gel formation is shown in Figure 1 .
[0118] In the following examples, the PVA-CA guest coordination gel and the PVA-CD host coordination gel were prepared by the following method:
[0119] 1. Dissolve 2-6 g PVA in 20-50 ml 60-80 ° C dimethyl sulfoxide (DMSO);
[0120] 2. Add 200-1000 mg of succinic anhydride and 1-50 mg of p-toluenesulfonic acid to the solution and react at 40-80°C for 24-72 hours;
[0121] 3. The precipitate was washed out with ether and dialyzed for 5 days to remove impurities, obtaining 2-5 g of PVA-Acid with a yield of 80-90%.
[0122] (II) Cholic acid grafting of polyvinyl alcohol
[0123] 1. Dissolve 200-1000 mg PVA-Acid in 20-50 ml 60-100°C dimethylformamide (DMF);
[0124] 2. Add 50-200 mg of aminocholic acid (Amino-CA), 1-100 mg of N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), and 1-20 mg of 1-hydroxybenzotriazole hydrate (HOBt) to the above solution and react at 50-80°C for 6-48 hours;
[0125] 3. Move the solution into an ice water bath to terminate the reaction, wash out the precipitate with ether, dialyze for 5-7 days to remove impurities, and dry to obtain PVA-CA.
[0126] (III) Cyclodextrin grafting of polyvinyl alcohol
[0127] 1. Dissolve 200-1000 mg PVA-Acid in 20-100 ml ultrapure water at 60-100°C;
[0128] 2. Add 100-800 mg aminocyclodextrin (Amino-CD), 20-100 mg EDC, and 1-20 mg HOBt to the above solution, stir for one hour, and react at 50-80°C for 6-48 hours;
[0129] 3. Move the solution into an ice water bath to terminate the reaction, wash out the precipitate with ether, dialyze for 5-7 days to remove impurities, and dry to obtain PVA-CD.
[0130] The PVA-CA and PVA-CD obtained by the above method were respectively added with water to prepare 10wt% (0.1g / g) PVA-CA gel solution and 10wt% (0.1g / g) PVA-CD gel solution, which were used in the preparation of the following examples and comparative examples to examine the physical and chemical properties of the gel of the present invention.
[0131] Example 1
[0132] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0133] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0134] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0135] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0136] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0137] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0138] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0139] The adhesion strength is 5.05 kPa, the 90-day degradation rate is 65.2%, and the LCST is 38 °C.
[0140] Example 2
[0141] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0142] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 60 g of acrylamide, 10 g of propylene sulfonic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 120 g of polydopamine in a three-necked flask;
[0143] 2. After stirring for one hour under nitrogen, add 10g of initiator ammonium persulfate and 20g of initiator tetramethylethylenediamine, and react at 80°C for 4h;
[0144] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AMPS-Al 3+ Gel solution.
[0145] 4. 500g polydopamine-PNIPAM-AM-AMPS-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 160 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0146] 5. Inject 240 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0147] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0148] The adhesion strength is 5.96 kPa, the 90-day degradation rate is 64%, and the LCST is 41.6 °C.
[0149] Example 3
[0150] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: put 500 g of N-isopropylacrylamide, 60 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 30 g of anthocyanin into a three-necked flask;
[0151] 2. After stirring for one hour under nitrogen, add 20g of initiator ammonium persulfate and 20μl of initiator tetramethylethylenediamine, and react at 50℃ for 12h;
[0152] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain anthocyanin-PNIPAM-AM-AA-Fe 3+ Gel solution.
[0153] 4. 500g anthocyanidin-PNIPAM-AM-AA-Fe 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0154] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0155] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0156] The adhesion strength is 4.66 kPa, the 90-day degradation rate is 65.1%, and the LCST is 41.2 °C.
[0157] Example 4
[0158] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0159] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 20 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0160] 2. After stirring for one hour under nitrogen, add 10g initiator ammonium persulfate and 5g initiator tetramethylethylenediamine, and react at 60°C for 7h;
[0161] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0162] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0163] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0164] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0165] The adhesion strength is 5.05 kPa, the 90-day degradation rate is 65.2%, and the LCST is 36.7 °C.
[0166] Example 5
[0167] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0168] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 55 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine in a three-necked flask;
[0169] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0170] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0171] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0172] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0173] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0174] The adhesion strength is 5.16 kPa, the 90-day degradation rate is 64.3%, and the LCST is 39.3 °C.
[0175] Example 6
[0176] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0177] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 2 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine in a three-necked flask;
[0178] 2. After stirring for one hour under nitrogen, add 10g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 65°C for 8h;
[0179] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0180] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 150 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0181] 5. Inject 250 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0182] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0183] The adhesion strength is 5.02 kPa, the 90-day degradation rate is 72.2%, and the LCST is 38 °C.
[0184] Example 7
[0185] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0186] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 40 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0187] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0188] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0189] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0190] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0191] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0192] The adhesion strength is 5.12 kPa, the 90-day degradation rate is 62.6%, and the LCST is 38 °C.
[0193] Example 8
[0194] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0195] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 30 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine in a three-necked flask;
[0196] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0197] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0198] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0199] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0200] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0201] The adhesion strength is 5.01 kPa, the degradation rate is 63.2% after 90 days, and the LCST is 38 °C.
[0202] Example 9
[0203] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0204] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, 40 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine in a three-necked flask;
[0205] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0206] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0207] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 250 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0208] 5. Inject 350 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0209] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0210] The adhesion strength is 5.19 kPa, the 90-day degradation rate is 60.4%, and the LCST is 38 °C.
[0211] Example 10
[0212] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0213] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 15 g of polydopamine in a three-necked flask;
[0214] 2. After stirring for one hour under nitrogen, add 10g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 60°C for 7h;
[0215] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0216] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0217] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0218] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0219] The adhesion strength is 4.05 kPa, the 90-day degradation rate is 65.2%, and the LCST is 38 °C.
[0220] Embodiment 11
[0221] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0222] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0223] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0224] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0225] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 100 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0226] 5. Inject 150 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0227] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0228] The adhesion strength is 5.35 kPa, the 90-day degradation rate is 69.3%, and the LCST is 38 °C.
[0229] Example 12
[0230] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0231] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 10 g of poloxamer 188, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine in a three-necked flask;
[0232] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0233] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0234] 4. 500g polydopamine-PNIPAM-AM-AA-Al3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0235] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0236] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0237] The adhesion strength is 5.09 kPa, the degradation rate is 69.7% in 90 days, and the LCST is 40.2° C. When poloxamer is used to replace acrylamide, it is found that the strength of the gel is lower than that of the gel obtained by adding acrylamide, and the degradation rate is also higher than that of the gel obtained by adding acrylamide.
[0238] Comparative Example 1
[0239] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0240] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 200 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0241] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0242] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0243] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0244] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0245] 6. Inject the above mixed solution A into 50 ml of water to obtain a gel.
[0246] The adhesion strength is 5.01 kPa, and the 90-day degradation rate is 63.6%. The AM value of the gel obtained in this comparative example is relatively high and does not have temperature-sensitive properties.
[0247] Comparative Example 2
[0248] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0249] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 45 g of acrylamide, 100 g of acrylic acid, 5 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 30 g of polydopamine in a three-necked flask;
[0250] 2. After stirring for one hour under nitrogen, add 5g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 12h;
[0251] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0252] The gel solution obtained in this comparative example did not gel. The reason for this was probably that the AA value was too high and it was not easy to gel.
[0253] Comparative Example 3
[0254] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0255] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 40 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 30 g of tannic acid are placed in a three-necked flask;
[0256] 2. After stirring for one hour under nitrogen, add 5g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 60°C for 7h;
[0257] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0258] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 200 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0259] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0260] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0261] The adhesion strength is 4.88 kPa, the degradation rate is 64.7% in 90 days, and the LCST is 38.5 °C. The gel obtained in this comparative example does not contain Al 3+ It does not have a self-healing effect and the cross-linking strength becomes lower.
[0262] Comparative Example 4
[0263] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0264] Prepare poly (N-isopropylacrylamide)-acrylamide gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 50 g of polydopamine are placed in a three-necked flask;
[0265] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0266] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0267] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution (30 wt%, ie, 0.3 g / g) and 50 g of PVA-CA guest coordination gel solution (10 wt%) were mixed to obtain a mixed solution A.
[0268] 5. Inject 100 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0269] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0270] The adhesion strength is 4.97 kPa, the degradation rate in 90 days is 70.3%, and the LCST is 38.6° C. It is found that the adhesion strength of the comparative example is reduced due to the low amount of PVA added.
[0271] Comparative Example 5
[0272] 1. Prepare poly (N-isopropylacrylamide)-acrylamide-acrylic acid gel solution using a one-pot method: put 500 g of N-isopropylacrylamide, 30 g of acrylamide, 20 g of acrylic acid, and 20 g of aluminum chloride (to be prepared into a 90 mg / g solution) into a three-necked flask;
[0273] 2. After stirring for one hour under nitrogen, add 15g of initiator ammonium persulfate and 10g of initiator tetramethylethylenediamine, and react at 50°C for 7h;
[0274] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain polydopamine-PNIPAM-AM-AA-Al 3+ Gel solution.
[0275] 4. 500g polydopamine-PNIPAM-AM-AA-Al 3+ The gel solution and 200 g of PVA-CA guest coordination gel solution (10 wt %) were mixed to obtain a mixed solution A.
[0276] 5. Inject 300 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0277] 6. Inject the above mixed solution A into 500 ml of water to obtain a gel.
[0278] The adhesion strength was 1.23 kPa, the degradation rate in 90 days was 64.6%, and the LCST was 38.2° C. Since the gel obtained in this comparative example did not contain polydopamine, the adhesion strength was low.
[0279] Comparative Example 6
[0280] 1. Dopamine hydrochloride was subjected to self-polymerization reaction at pH = 11 for 30 minutes to obtain polydopamine, at which time the solution changed from transparent to black.
[0281] Prepare poly (N-isopropylacrylamide)-acrylamide-acrylic acid gel solution using a one-pot method: 500 g of N-isopropylacrylamide, 30 g of acrylamide, 5 g of acrylic acid, 20 g of aluminum chloride (need to be prepared into a 90 mg / g solution), and 30 g of polydopamine in a three-necked flask;
[0282] 2. After stirring for one hour under nitrogen, add 5g of initiator ammonium persulfate and 50μl of initiator tetramethylethylenediamine, and react at 60℃ for 7h;
[0283] 3. The gel solution was dialyzed for 7 days to remove impurities and obtain PNIPAM-AM-AA-Al 3+ Gel solution.
[0284] 4. 500g polydopamine-PNIPAM-AM-AA-Al3+ The gel solution and 400 g of PVA-CA guest coordination gel solution (10 wt %) were mixed to obtain a mixed solution A.
[0285] 5. Inject 500 g of PVA-CD host coordination gel solution (10 wt%) into 500 ml of water;
[0286] 6. Inject the mixed solution A into 500 ml of bile to obtain a gel.
[0287] The adhesion strength is 4.05 kPa, the degradation rate in 90 days is 46.1%, and the LCST is 38° C. Since the proportion of PVA in the gel obtained in this comparative example is large and the proportion of polydopamine is reduced, the adhesion strength is low; and the proportion of PVA is increased, the degradation rate of the material decreases.
[0288] When studying the gel system of the present invention, the inventors prepared a number not limited to the aforementioned embodiments and comparative examples, and examined and confirmed the raw materials, ratio relationship and preparation method of the gel system of the present invention through the structure, adhesion strength, degradation curve, self-healing properties and temperature sensitivity of the gel system under an electron microscope.
[0289] For example, if dopamine hydrochloride is reacted at a pH value lower than 10, even after a long reaction time (6 hours), the solution remains transparent without any color change, and polydopamine with enhanced self-healing properties cannot be prepared. The transparent dopamine solution prepared at a pH value lower than 10 has extremely poor self-healing properties or even no self-healing properties even if the gel is obtained according to the formula and preparation method of Example 1.
[0290] like Figure 2 ,, taking the gel system prepared in Example 1 as an example, a 1000-fold pore structure image was taken by scanning electron microscopy, which shows that the gel of the present invention is entangled and cross-linked in physical space and has a large pore structure.
[0291] like Figure 3 Taking Example 1 as an example, a small piece of gel (about 1 g) was cut to observe its actual adhesion ability. The hydrogel can adhere to the gloves without falling off; and can adhere to the cap of the centrifuge tube without falling off.
[0292] like Figure 4 , the degradation curves of the gel-forming gels in Examples 1-12 and Comparative Examples 1-6 were investigated (see Figure 4 A- Figure 4Q), observe the degradation of each gel within 90 days. Experimental method: Take 5g of gel, record the weight of the gel at this time as W initial, put it into 37℃, 200ml bile to simulate in vivo degradation experiment, take out the gel after a period of time, measure the weight of the gel at this time after 24h of constant humidity and constant weight, and calculate the degradation rate. The results show that compared with the existing gel made of similar raw materials, the degradation time of the gel system of the present invention is significantly improved, and it can maintain a degradation time of at least three months in bile.
[0293] like Figure 5 Taking Example 1 as an example, the prepared gel was cut into small pieces and taken out, and the taken out gel was divided into two parts using a scalpel. Then the cut surfaces of the two small pieces of gel were aligned, and the self-healing conditions were observed every 1 hour. Figure 5 It can be seen that as time goes by, the gel is gradually healing, the adhered part of the cut surface is getting larger and larger, and after 6-8 hours it heals into a whole again.
[0294] like Figure 6 Taking Example 1 and Comparative Example 1 as examples, the three mixed gel solutions were mixed and placed in a water bath, and the temperature was gradually raised from 32°C to 42°C. Each temperature was kept for 30 minutes, and the end point was determined when the bottle was tilted and the gel solidified. Finally, it was found that Example 1 gelled at about 38°C, while Comparative Example 1 could not gel at 42°C. This shows that the amount of acrylamide added has a clear effect on the regulation of the LCST value.
[0295] Through the above-mentioned embodiments, comparative examples and other screening examples, the raw material composition and dosage ratio of the gel system of the present invention are finally determined. The preparation method, raw material composition and dosage relationship of each gel solution are as described in the invention content, which can make the mixed gel have two response characteristics of temperature sensitivity and host-guest coordination. It is an aqueous solution at room temperature and becomes a hydrogel at a predetermined temperature. It can be maintained for a certain period of time before degrading, and the material can be applied in a wider range of fields.
Claims
1. Dual dual response gel system, characterized by: The gel system is divided into a first layer of gel and a second layer of gel, wherein: The first layer of gel is composed of poly (N-isopropylacrylamide)-acrylamide gel solution and guest coordination gel solution; The second layer of gel is a main coordination gel solution; wherein the guest coordination gel solution is a polyvinyl alcohol-cyclodextrin gel solution; The main coordination gel solution is one or more of polyvinyl alcohol-bile acid gel solution, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution, and polyvinyl alcohol-glycine gel solution.
2. The dual dual response gel system according to claim 1, characterized in that: At least one of the following is met: The weight ratio of each gel solution is calculated based on the amount of solid content: According to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, add 10-25g of poly (vinyl alcohol)-cyclodextrin gel and 15-30g of main coordination gel; Or preferably, according to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, 10-25g of poly (vinyl alcohol)-cyclodextrin gel and 20-30g of main coordination gel are added; Or, according to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, add 10-25g of poly (vinyl alcohol)-cyclodextrin gel and 15-30g of poly (vinyl alcohol)-bile acid gel; Or preferably, according to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, 15-25g of poly (vinyl alcohol)-cyclodextrin gel and 20-30g of poly (vinyl alcohol)-bile acid gel are added; Or most preferably, according to every 150g poly (N-isopropylacrylamide)-acrylamide gel, 20g poly (vinyl alcohol)-cyclodextrin gel and 30g poly (vinyl alcohol)-bile acid gel are added; Or, according to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, add 10-25g of poly (vinyl alcohol)-cyclodextrin gel, 15-30g of one or more of polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel; Or preferably, according to every 150g of poly (N-isopropylacrylamide)-acrylamide gel, 15-25g of poly (vinyl alcohol)-cyclodextrin gel, 20-30g of one or more of polyethylene glycol-bile acid gel, poly (vinyl alcohol)-deoxycholic acid gel, poly (vinyl alcohol)-taurocholic acid gel or poly (vinyl alcohol)-glycine gel are added; Or most preferably, 20 g of polyvinyl alcohol-cyclodextrin gel, 30 g of polyethylene glycol-bile acid gel, polyvinyl alcohol-deoxycholic acid gel, polyvinyl alcohol-taurocholic acid gel or polyvinyl alcohol-glycine gel are added per 150 g of poly (N-isopropylacrylamide)-acrylamide gel.
3. The dual dual response gel system according to claim 1, characterized in that: At least one of the following is met: When the gel system is used, each gel is first prepared into a gel solution before use, wherein: The concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.1-0.5 g / g; Or preferably, the concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.1-0.3 g / g; Or most preferably, the concentration of the poly (N-isopropylacrylamide)-acrylamide gel solution is 0.3 g / g; Or, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.05-0.15 g / g; Or preferably, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.05-0.1 g / g; Or most preferably, the concentration of the polyvinyl alcohol-cyclodextrin gel solution is 0.1 g / g; Or, the main coordination gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.05-0.15g / g; Or preferably, the main coordination gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.05-0.1g / g; Or most preferably, the main gel solution adopts one or more of polyethylene glycol-bile acid gel, polyethylene glycol-bile acid gel solution, polyvinyl alcohol-deoxycholic acid gel solution, polyvinyl alcohol-taurocholic acid gel solution or polyvinyl alcohol-glycine gel solution, and its concentration is 0.1g / g; Or preferably, the main coordination gel solution adopts polyethylene glycol-bile acid gel solution, and its concentration is 0.05-0.15g / g; Or further preferably, the main coordination gel solution adopts polyethylene glycol-bile acid gel solution, and its concentration is 0.05-0.1g / g; Or most preferably, the main gel solution adopts polyethylene glycol-bile acid gel solution with a concentration of 0.1 g / g.
4. The dual dual response gel system according to any one of claims 1 to 3, characterized in that: The poly (N-isopropylacrylamide)-acrylamide gel solution is prepared by a one-pot method: A. Weigh the reaction raw materials N-isopropylacrylamide, acrylamide, carboxyl donor, chloride salt, and polyphenol group donor according to proportion and place them in a reaction device; B. After passing inert gas into the reaction device and stirring for a certain period of time, add initiator ammonium persulfate and accelerator tetramethylethylenediamine to obtain gel solution B; C. The gel solution obtained in step B is dialyzed to remove impurities, thereby obtaining a poly (N-isopropylacrylamide)-acrylamide gel solution.
5. The dual dual response gel system according to claim 4, characterized in that: At least one of the following is met: The acrylamide in the reaction raw material of step A can be replaced by one or more of poloxamer and polylactic acid-glycolic acid-ethylene glycol; Or, the carboxyl donor in the reaction raw material of step A is one or more of acrylic acid, propylene sulfonic acid, and itaconic acid; Or, the chloride salt in the reaction raw material of step A is used as the metal ion donor, and the chloride salt that can be used is one or more of aluminum chloride, ferric chloride, and calcium chloride; Or, the polyphenol group donor in the reaction raw material of step A is one or more of polydopamine, tannic acid, and anthocyanin; Alternatively, the polydopamine is prepared by the following method: using dopamine hydrochloride, a self-polymerization reaction is carried out under the condition of pH = 10-12, and when the solution changes from transparent to black, the reaction is considered to be complete, and polydopamine is obtained; Or preferably, in the polydopamine preparation method, the pH value is 11-12; Or most preferably, in the polydopamine preparation method, the pH value is 11. Or preferably, in the polydopamine preparation method, the self-polymerization reaction time is 20-60 min; preferably, the self-polymerization reaction time is 30-60 min; most preferably, the self-polymerization reaction time is 30 min. Or the reaction raw material ratio relationship described in step A: The reaction raw materials in step A are added with 10-80 g of acrylamide or one or more of poloxamer, polylactic acid-glycolic acid-ethylene glycol, 1-50 g of carboxyl donor, 90-450 mg of chloride salt, and 1-120 g of polyphenol group per 500 g of N-isopropylacrylamide; Or preferably, the reaction raw materials in step A are added with 20-60g acrylamide, 10-30g poloxamer or 20-40g polylactic acid-glycolic acid-ethylene glycol per 500g N-isopropylacrylamide; the carboxyl donor is 1-30g acrylic acid, 1-20g propylene sulfonic acid or 1-20g itaconic acid; the chloride salt is 90-270mg aluminum chloride, 90-270mg ferric chloride or 90-270mg calcium chloride; the polyphenol group is 1-50g polydopamine, 5-30g tannic acid or 1-30g anthocyanin; Or most preferably, in step A, 30 g of acrylamide is added to the reaction raw materials per 500 g of N-isopropylacrylamide; 20 g of acrylic acid is used as the carboxyl donor; 180 mg of aluminum chloride is used as the chloride salt; and 50 g of polydopamine, 5-30 g of tannic acid, or 1-30 g of anthocyanin is used as the polyphenol group; In step B, the amount of the initiator ammonium persulfate and the accelerator tetramethylethylenediamine is calculated based on 1-20g of initiator ammonium persulfate and 1-20g of accelerator tetramethylethylenediamine per 500g of N-isopropylacrylamide; Or preferably, the amount of the initiator ammonium persulfate and the accelerator tetramethylethylenediamine in step B is calculated based on 15g of initiator ammonium persulfate and 10g of accelerator tetramethylethylenediamine per 500g of N-isopropylacrylamide; Alternatively, the aeration and stirring for a certain period of time in step B refers to stirring for 0.5-2 hours; preferably, the stirring time in step B is 1 hour; Alternatively, the reaction conditions of the reaction in step B are: reaction temperature 40-80°C, reaction time 4-12h; preferably, the reaction conditions of step B are: reaction temperature 60°C, reaction time 6h; Or, the dialysis in step C is water dialysis, and the dialysis time is 5-7 days; Or preferably, the dialysis time in step C is 7 days; Alternatively, the solution obtained in step C is dried to obtain poly (N-isopropylacrylamide)-acrylamide gel; Or preferably, the drying in step C is carried out by low-temperature oven drying or freeze drying.
6. The dual dual response gel system according to any one of claims 1 to 3, characterized in that: The preparation method of the polyvinyl alcohol-cyclodextrin gel solution comprises the following steps: A. Acidification modification of polyvinyl alcohol: (1) Polyvinyl alcohol is dissolved in dimethyl sulfoxide; (2) adding succinic anhydride and p-toluenesulfonic acid to the solution obtained in step (1) to react; (3) adding ether to the reaction solution obtained in step (2), filtering and washing to obtain a precipitate, dialyzing the precipitate with water to remove impurities, and drying to obtain acid-modified polyvinyl alcohol; B. Cyclodextrin grafting of polyvinyl alcohol (1) Acid-modified polyvinyl alcohol is dissolved in water; (2) adding aminocyclodextrin, N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, and 1-hydroxybenzotriazole hydrate to the solution obtained in step (1), stirring for a certain period of time, reacting, and cooling to terminate the reaction; (3) Ether is added to the solution obtained in step (2) to wash out the precipitate, and the precipitate is dialyzed to remove impurities to obtain polyvinyl alcohol grafted cyclodextrin.
7. The dual dual response gel system according to claim 6, characterized in that: At least any one of the following is satisfied: In the acidification modification of polyvinyl alcohol in step A: The polyvinyl alcohol and dimethyl sulfoxide in step (1) are mixed according to the following ratio: 20-50 ml of dimethyl sulfoxide is added for every 2-6 g of polyvinyl alcohol; Preferably, the polyvinyl alcohol and dimethyl sulfoxide in step (1) are mixed according to the following ratio: 50 ml of dimethyl sulfoxide is added for every 4 g of polyvinyl alcohol; The amount of succinic anhydride and p-toluenesulfonic acid added in step (2) is 200-1000 mg succinic anhydride and 1-50 mg p-toluenesulfonic acid per 2-6 g polyvinyl alcohol; Preferably, the amount of succinic anhydride and p-toluenesulfonic acid added in step (2) is 400-500 mg succinic anhydride and 5-25 mg p-toluenesulfonic acid per 4 g polyvinyl alcohol; The temperature of the dimethyl sulfoxide (DMSO) in step (1) is 60-90°C, that is, polyvinyl alcohol is dissolved in dimethyl sulfoxide at 60-90°C; preferably, the temperature of the dimethyl sulfoxide (DMSO) in step (1) is 80°C; The reaction conditions of step (2) are: reaction temperature 40-80°C, reaction time 36-72h; preferably, the reaction conditions of step (2) are reaction temperature 50°C, reaction time 48h; The dialysis conditions in step (3) are: dialysis with water for 5-7 days; preferably, the dialysis time is 5 days; The drying in step (3) is carried out by low temperature oven drying or freeze drying; In the step B of cyclodextrin grafting of polyvinyl alcohol: The water in step (1) is ultrapure water; The temperature of the water in step (1) is 70-90° C., that is, the acidified modified polyvinyl alcohol is dissolved in water at 70-90° C.; preferably, the temperature of the water in step (1) is 80° C.; The stirring for a certain time in step (2) refers to stirring for 0.5-2 hours; preferably, the stirring for a certain time in step (2) refers to stirring for 1 hour; The reaction conditions of the reaction in step (2) are: reaction temperature 40-80°C, reaction time 8-36h; preferably, the reaction conditions of the reaction in step (2) are: reaction temperature 70°C, reaction time 24h; The step (2) of cooling the reaction to terminate the reaction is to move the reaction solution into an ice water bath to terminate the reaction; The dialysis in step (3) is water dialysis, and the dialysis time is 5-7 days; preferably, the dialysis time in step (3) is 7 days.
8. The dual dual response gel system according to any one of claims 1 to 3, characterized in that: The preparation method of the polyvinyl alcohol-bile acid gel solution comprises the following steps: A. Acidification modification of polyvinyl alcohol (1) Polyvinyl alcohol is dissolved in dimethyl sulfoxide; (2) adding succinic anhydride and p-toluenesulfonic acid to the solution obtained in step (1) to react; (3) adding ether to the reaction solution obtained in step (2), filtering and washing to obtain a precipitate, dialyzing the precipitate with water to remove impurities, and drying to obtain acid-modified polyvinyl alcohol; B. Bile acid grafting of polyvinyl alcohol (1) Acid-modified polyvinyl alcohol is dissolved in dimethylformamide; (2) adding aminocholic acid, N(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, and 1-hydroxybenzotriazole hydrate to the solution obtained in step (1), stirring for a certain period of time, reacting, and cooling to terminate the reaction; (3) Ether is added to the solution obtained in step (2) to wash out the precipitate, and the precipitate is dialyzed to remove impurities to obtain polyvinyl alcohol-grafted bile acid.
9. The dual dual response gel system according to claim 8, characterized in that: At least any one of the following is satisfied: In the bile acid grafting of polyvinyl alcohol in step B: The temperature of the dimethylformamide in step (1) is 70-90° C., that is, the acidified modified polyvinyl alcohol is dissolved in dimethylformamide at 70-90° C.; preferably, the temperature of the dimethylformamide in step (1) is 80° C.; The stirring time in step (2) refers to stirring for 0.5-2 hours; preferably, the stirring time in step (2) is 1 hour; The reaction conditions of the reaction in step (2) are: reaction temperature 40-80°C, reaction time 8-36h; preferably, the reaction conditions of the reaction in step (2) are: reaction temperature 70°C, reaction time 24h; The step (2) of cooling the reaction to terminate the reaction is to move the reaction solution into an ice water bath to terminate the reaction; The dialysis in step (3) is water dialysis, and the dialysis time is 5-7 days; preferably, the dialysis time in step (3) is 7 days.
Citation Information
Cited By
Hydrogel with controllable and enhanced mechanical properties as well as preparation and application of hydrogel
CN119708545A
A hydrogel with controllable enhanced mechanical properties, its preparation and application
CN119708545B
Planting method for improving afforestation survival rate of sand bare-rooted seedlings
CN120584694A